Implications of alternative mitigation policies on world prices for fossil fuels and agricultural products - Sergey Paltsev (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Emissions mitigation policies affect prices, including prices for fossil fuels and agricultural products. Consumer prices for coal and natural gas are expected to rise when climate policy is implemented, while oil prices may be reduced or remain the same in comparison to a no policy scenario. Impacts on agricultural prices are more controversial as reduced negative productivity impacts on yields are compensated by increased costs of energy inputs to agriculture, lower CO2 fertilization effect, and a competition for land from biofuels. In most of the mitigation scenarios considered in the paper, mitigation policies increase agricultural prices in comparison to the no policy scenario.
Keywords: Q54; Q47; Q18; 330; climate change mitigation; fuel prices; agricultural prices; biofuels; computable general equilibrium; Klimawandel; Immissionsschutz; Fossile Energie; Biokraftstoff; Agrarpreis; CGE-Modelling; Allgemeines Gleichgewicht